Synthesis of ferrocenylphenyl derivatives including biphenylferrocenes, arylferrocenylphenyl ethers and arylferrocenylphenyl amines - Imrie, Christopher; Engelbrecht, Pieter; Loubser, Christa; McCleland, Cedric W; Nyamori, Vincent O; Bogardi, Robert; Levendis, Demetrius C; Tolom, Nomfuneko; van Rooyen, Jason; Williams, Nadia (Journal of organometallic chemistry, 2002)
The preparation of a series of substituted biphenylferrocenes via a modified Suzuki reaction between 4-bromophenylferrocene and substituted phenylboronic acids is described. The X-ray crystal structure of 4′-formyl-4-biphenylferrocene is reported and this compound is then incorporated into the first series of ferrocenomesogens containing the ferrocenylbiphenyl unit. The synthesis of a series of arylferrocenylphenyl ethers and arylferrocenylphenyl amines is also described. The reaction of 4-bromophenylfererrocene with substituted phenylboronic acids provides excellent yields of substituted biphenylferrocenes. The synthesis of arylferrocenylphenyl ethers and arylferrocenylphenyl amines has been achieved. The X-ray structure of 4′-formyl-4-biphenylferrocene has been determined. A series of ferrocenomesogens has been prepared from 4′-formyl-4-biphenylferrocene.